The Levels of Tumor Necrosis Factor-Alpha and Interleukin-6 in Patients with Isolated Coronary Artery Ectasia - Mustafa Aydin; Ishak Ozel Tekin; Sait Mesut Dogan; Nesligul Yildirim; Mehmet Arasli; Muhammet Rasit Sayin; Ziyaettin Aktop (Mediators of Inflammation)
Background/Aim. Coronary artery ectasia (CAE) is considered as a variant of atherosclerosis. Tumor necrosis factor-alpha (TNF-𝛼) and interleukin-6 (IL-6) are among the sensitive markers of systemic inflammation. The aim of this study was to evaluate the plasma levels of the cytokines; TNF-𝛼 and IL-6 in CAE patients. Methods. Plasma concentrations of TNF-𝛼 and IL-6 were measured in 36 patients with CAE (28 males, mean age: 58.2±12 years), and results were compared with age and sex-matched controls (n=32) without coronary artery ectasia. TNF-𝛼 and IL-6 concentrations in blood were assesed by enzyme-linked immunosorbent assay (ELISA). Results. Baseline characteristics of the two groups were similar. TNF-𝛼 and IL-6 levels were significantly higher in CAE group than controls (15.6±11.2 pg/mL versus 7.8±3.7 pg/mL, 𝑃<.001, and 17.2±12.6 versus 7.6±2.1 𝑃<.0001, resp.). Conclusion. CAE patients showed increases in TNF-𝛼 and IL-6 levels compared to the controls. This study provides evidence for alterations in the proinflamatory cytokines which suggest the involvement of the immune system in the pathophysiology of CAE. Further placebo-controlled studies are needed to evaluate the clinical significance of this increase in TNF-𝛼 and IL-6 levels.